Estrés académico y consumo de sustancias en estudiantes universitarios de América Latina - Arias Largo, Jandry Santiago (2024)
The present study has as its general objective to establish scientific evidence on academic stress and its influence on substance use in university students in Latin America. Throughout the research, various dimensions of academic stress are addressed, as well as the implications that this phenomenon has on substance use behavior in this population group. In the first specific objective, the prevalence of academic stress among students from various higher education institutions in Latin America is identified. Through quantitative and qualitative methodologies, the magnitude of the problem is analyzed, revealing that a significant number of students face high levels of stress that could compromise their wellbeing. The second specific objective focuses on the stages of substance use, where the pattern of use among university students is examined. Different categories of consumers are identified, from those who initiate their consumption at experimental levels to those who develop problematic patterns of use, highlighting how academic stress can act as a facilitator in these processes. Finally, the risk factors associated with substance use are identified, such as academic pressure, lack of social support, and family expectations, among others. This part of the study emphasizes the importance of understanding the contexts in which both stress and substance use occur. To contribute to the prevention and management of these problems, an informative guide on addictive behaviors and academic stress will be designed, aimed at students, educators and health professionals. This guide is based on the findings obtained and seeks to provide effective strategies to address stress and minimize the risk of substance use